2002
DOI: 10.1002/jmv.10149
|View full text |Cite
|
Sign up to set email alerts
|

SEN virus infection does not affect the progression of non‐A to ‐E liver disease

Abstract: SEN virus (SEN V) was discovered recently as a potential causative agent of non-A, non-B, non-C, and non-E (non-A to -E) hepatitis. The aim of this study was to obtain information about the prevalence of this virus in Japan and its association with non-A to -E liver disease. Sixty-seven patients hospitalized for non-A to -E liver disease, including hepatocellular carcinoma (19 patients), cirrhosis (7 patients), chronic hepatitis (18 patients), and acute hepatitis (23 patients), were tested, along with 49 blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
2

Year Published

2004
2004
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 8 publications
2
27
2
Order By: Relevance
“…The prevalence of GBV-C RNA among our patients overall was as low as the overall infection rate in the Japanese population (0.8%). 40 The prevalence of SENV DNA has been reported to be 28.6% in blood donors and 49.3% in patients with non-A to -E liver disease, 41 and the prevalence of SENV in our subjects was similar to the latter figure. These results suggest that neither GBV-C infection nor SENV infection are involved in the development and progression of NAFLD.…”
Section: Discussionsupporting
confidence: 84%
“…The prevalence of GBV-C RNA among our patients overall was as low as the overall infection rate in the Japanese population (0.8%). 40 The prevalence of SENV DNA has been reported to be 28.6% in blood donors and 49.3% in patients with non-A to -E liver disease, 41 and the prevalence of SENV in our subjects was similar to the latter figure. These results suggest that neither GBV-C infection nor SENV infection are involved in the development and progression of NAFLD.…”
Section: Discussionsupporting
confidence: 84%
“…Another report, Sugiura et al[ 18], in Japan reported that the two variants are not associated with acute or chronic hepatitis, although SENV-D might be a risk factor of fulminant hepatitis. Nevertheless, other studies have found only a weak association between SENV infection and liver disease [19,20,21]. In this study, no significant association was found between SENV infection and persistent elevated ALT value due to HBV/HCV infection or non-HBV/HCV origin, suggesting that the presence of SENV did not cause more severe liver damage in our patient group.…”
Section: Discussioncontrasting
confidence: 45%
“…In the last two years, several studies, performed in Europe, Asia, and North America, have evaluated the prevalence, modes of transmission and clinical relevance of SENV (Shibata et al 2001, Unemura et al 2001, Kao et al 2002, Mikuni et al 2002, Pirovano et al 2002a,b, Yoshida et al 2002, Schröter et al 2002. However, few data are available regarding the circulation of SENV strains in South America.…”
mentioning
confidence: 99%